Best Answer

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals" etc. Also use ^ to indicate powers (eg x-squared = x^2).

Q: What is the value of x if 2x y 8 and 2x - 3y - 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x plus 3y is not an equation, it is an expression.

Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7

x=1y=2x+3y=2*1 + 3y=5

-2x+8=3y(-2x+8)/3=yplug in values of x or y into equation to find x or yTo obtain specific values for x or y, you would need 2 equations for the two variables. You can still solve the equation for a specific variable, in terms of the other. For example, to solve for x:2x + 3y = 82x = 8 - 3yx = (8 - 3y) / 2

2x+3y = 6 2x+3(0) = 6 2x = 6 x = 6/2 x = 3

Related questions

If: 2x-3y = -15 and x = 4y Then: x = -12 and y = -3

x + 3y = 2 2x - 3y = 22 Add the two equations: 3x = 24 Divide both sides by 3 to give x= 8. Substitue this value of x in the first equation to give 8 + 3y = 2 Subtract 8 from both sides: 3y = -6 Divide both sides by 3: y = -2 Solution: (X, y) = (8, -2)

2x plus 3y is not an equation, it is an expression.

x-intercept:2x = 24x = 12y-intercept:-3y = 24y = -8

4xyÂ²(3y-x)-2xÂ²(x-3y)Â²=4xyÂ²(x-3y)-2xÂ²(x-3y)Â²=(x-3y)[4xyÂ²-2xÂ²(x-3y)Â²]=(x-3y)(4xyÂ²-2xÂ³+6xÂ²y)=(x-3y)(-2xÂ³+6xÂ²y+4xyÂ²)=-2x(x-3y)(xÂ²-3xy-2yÂ²)= -2x(x-3y)(x-y)(x-2y)

Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7

x=1y=2x+3y=2*1 + 3y=5

-2x+8=3y(-2x+8)/3=yplug in values of x or y into equation to find x or yTo obtain specific values for x or y, you would need 2 equations for the two variables. You can still solve the equation for a specific variable, in terms of the other. For example, to solve for x:2x + 3y = 82x = 8 - 3yx = (8 - 3y) / 2

We should always start with slope-intercept form: 2x + 3y = 24 3y = -2x + 24 y = -2x/3 + 8 Once in this form we see that our y-axis intercept is 8. To find our x-axis intercept, we solve the equation substituting 0 for y: 0 = -2x/3 + 8 -8 = -2x/3 x = (-8)(-3/2) x = 24/12 x = 12

2x+3y = 6 2x+3(0) = 6 2x = 6 x = 6/2 x = 3

4x + 3y = 1y = 2x + 8 Take the first part: 4x + 3y = 1y 4x = 1y - 3y 4x = -2y x = -y/2 Substitute x in second part: 1y = 2x + 8 1y = -2y/2 + 8 1y = -1y + 8 2y = 8 y = 4 Substitute y into either part: 1y = 2x + 8 1(4) = 2x + 8 4 - 8 = 2x -4 = 2x x = -2 Therefore: x = -2 y = 4

8